1999
DOI: 10.1063/1.124801
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced direct formation of C54 TiSi2 films with fine grains on c-Si substrates

Abstract: In this letter, we report on the direct synthesis of C54 TiSi2 films with fine grains by pulsed-laser irradiation from Ti deposited on Si substrates, using a Q-switched Nd:YAG laser. The films were characterized using micro-Raman spectroscopy, high-resolution transmission electron microscopy, and atomic force microscopy. In comparison with the C54 TiSi2 using the conventional rapid thermal annealing (RTA) of 35 nm thick Ti/Si, which has an average grain size of about 110 nm and film thickness of 50 nm, the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, this may not be the case for a single pulsed laser irradiation because the duration of annealing is in the regime of tens of nanoseconds. Although Chen et al 12 had reported that C54 TiSi 2 can be obtained using laser annealing without prior formation of the C49 phase, it should be mentioned that the laser system (a Q-switched Nd:YAG laser with a wavelength of 1.06 m) that was used in their experiment is different from the 248 nm pulsed excimer laser that was employed in this work. Hence, in our work, the heating mechanism during laser irradiation and duration of anneal (pulse duration) is different from that of Chen et al 12 Furthermore, they 12 postulated that C54 TiSi 2 was formed via a solid-state reaction between Ti and Si and that no melting had occurred during the laser irradiation.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, this may not be the case for a single pulsed laser irradiation because the duration of annealing is in the regime of tens of nanoseconds. Although Chen et al 12 had reported that C54 TiSi 2 can be obtained using laser annealing without prior formation of the C49 phase, it should be mentioned that the laser system (a Q-switched Nd:YAG laser with a wavelength of 1.06 m) that was used in their experiment is different from the 248 nm pulsed excimer laser that was employed in this work. Hence, in our work, the heating mechanism during laser irradiation and duration of anneal (pulse duration) is different from that of Chen et al 12 Furthermore, they 12 postulated that C54 TiSi 2 was formed via a solid-state reaction between Ti and Si and that no melting had occurred during the laser irradiation.…”
Section: Resultsmentioning
confidence: 84%
“…Owing to this unique characteristic, laser irradiation has been proposed to be used as an annealing technique to form thin silicided films with desirable electrical properties. [11][12][13][14] Talwar et al 14 have reported that laser annealing (with an additional RTA step) can form low resistivity TiSi 2 films on polysilicon gates with linewidths as small as 0.07 m and suggested that fine TiSi 2 grains can be formed after laser processing. However, detailed results of grain size analysis were not shown.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed laser annealing has also been investigated and several important benefits have been demonstrated. First, due to its fast ramping rate and short anneal duration, nanosecond laser annealing (UV-NLA) has been found to enable the formation of smaller grains of C49-TiSi2 than RTA [30][31][32] , increasing the density of C54-TiSi2 nucleation sites. Chen et al 30 have also reported that the transformation temperature into C54-TiSi2 can be significantly reduced by pulsed laser annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 30 have also reported that the transformation temperature into C54-TiSi2 can be significantly reduced by pulsed laser annealing. Moreover, the technologically favorable C54-TiSi2 phase has been obtained directly after the laser annealing step 30,32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Compared to the C54 TiSi 2 phase grown via rapid thermal annealing the grain size of the laser-grown C54 TiSi 2 phase is smaller, 1 which is highly desired for interconnects in the subquarter very large scale integration ͑VLSI͒ technology. Because of the high reactivity and the gettering properties of Ti, 2-6 it is extremely difficult to avoid oxygen contamination during the TiSi 2 fabrication even when the Ti deposition and interface annealing are performed under ultrahigh vacuum ͑UHV͒ conditions.…”
mentioning
confidence: 99%